The correlation between temporomandibular disorders, atypical swallowing and dyslalia - Alessandro Marchesi; Daniele D'Apote; Anna D'Apote; Riccardo Ciancaglini; Laura Strohmenger (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2019)
Background: Temporomandibular disorders are pathological conditions which involve temporomandibular joint. Their etiopathogenesis is multifactorial. Therefore it's interesting to analyse their correlation with other structures of the oral cavity such as tongue. The context and purpose of the study: to investigate the eventual correlations between temporomandibular disorders and atypical swallowing and between temporomandibular disorders and dyslalia in adult subjects. It is also studied the association between atypical swallowing and dyslalia in temporomandibular disorders and in healthy patients.  Main findings: this study shows that the prevalence of atypical swallowing in the group with TMD is greater than in the group without TMD. These results suggest the presence of atypical swallowing could be used to detect an increased risk of temporomandibular disorders.  Results: the prevalence of temporomandibular disorders among subjects with or without atypical swallowing is respectively 67.7% and 46.7%, being statistically significant. The prevalence of temporomandibular disorders among subjects with or without dyslalia is respectively 62.5% and 48.9%, resulting not statistically significant. The prevalence of dyslalias in subjects with atypical swallowing is 28.6% in the group with temporomandibular disorders and 30.0% in the group without temporomandibular disorders. Therefore our study confirms the association between atypical swallowing and dyslalia, regardless of the fact that the treated patients were affected by temporomandibular disorders.  Conclusion: To our knowledge, this is the first study that investigates the existence of associations between temporomandibular disorders and tongue position in swallowing and phono-articulation in the adult population.   Brief summery: an observational case-control study was conducted. The total sample consisted of 100 adult subjects with temporomandibular disorders and 100 healthy adult subjects. All patients underwent a gnatology test, using Helkimo disfunction index, a phonemic test linked to evaluation of spontaneous speech for dyslalias and they eventually underwent a swallowing test. Comparison between groups with and without TMD was made using the chi-square test or Fisher's exact test or test-parametric Mann-Whitney. Significance values p less than 0.05 were considered statistically significant.  Any potential implications: this study provides the basis for conducting further longitudinal studies to clarify the nature of the inter-relationships examined.